Identifikasi dan Kelimpahan Bakteri Pelarut Fosfat Dari Rizosfer Tanaman di Lahan Pasca Tambang Timah - Vania Putri; Ismed Inonu; Rahmad Lingga (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2026)
This study aimed to isolate and identify Phosphate-solubilizing Bacteria (PSB) from the rhizosphere of spinach, water spinach, and lamtoro grown on post-tin mining land in Padang Baru Village, Central Bangka Regency. Soil samples were collected from the rhizosphere and serially diluted before being cultured on Pikovskaya agar to isolate PSB, which were then characterized morphologically, physiologically, and biochemically. Biochemical tests included Gram staining, catalase, motility, methyl red (MR), and Triple Sugar Iron Agar (TSIA) tests, while phosphate solubilization activity was quantified using the Phosphate Solubilization Index (PSI). A total of seven isolates were successfully obtained and showed diverse colony morphologies, indicating adaptation to extreme post-mining conditions. The isolates were identified as belonging to the genera Pseudomonas, Rhodococcus, and Acinetobacter, known for solubilizing phosphate via organic acids and exopolysaccharides (EPS). Although the PSI values were in the moderate range, the high colony abundance demonstrated strong viability and ecological competitiveness. These research suggest that PSB from degraded post-mining soils may serve as potential biofertilizers to enhance phosphorus availability and support ecological rehabilitation.